HUBUNGAN PENDAMPING SUAMI DENGAN KALA DUA LAMA PADA IBU BERSALIN - Mutiara, Violita Siska; Wulandari, Elza; Rahmawati, Ida; Yusanty, Nidia (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Old labor is one of the fourth leading causes of maternal mortality in Indonesia. The incidence of old childbirth in 2007 and 2012 is still the same, namely 5%.This study aims to study the relationship between birth companion and the incidence of prolonged second stage of labor among women in labor. This study used a survey analytical research design with a cross sectional approach. The study sample were 124 women in labor in Sakura Ward of Central Bengkulu Regional Hospital in 2019, who were taken by total sampling. Data to be analysed in this study were secondary data, that were collected using a checklist and data collection form as the study instruments. The results showed that of the 124 mothers who gave birth, 28.2% experienced prolonged second stage of labor and 71.8% did not experience it, 46.8% were not accompanied by their husbands and 53.2 were accompanied by their husbands. There was a significant relationship between the presence of a birth companion and the incidence of prolonged second stage of labor among women in labor. Women in labor who were not accompanied by their husbands were at risk of experiencing prolonged second stage of labor by 3.529 times compared to them who were accompanied by their husbands. It was concluded that there was a significant relationship between husbands companion and the incidence prolonged second stage of labor among women in labor. It is expected that this study can improve health services and appropriate screening to the incidence of prolonged second stage of labor among women in labor. Furthermore, husbands are expected to be present as the birth companion.